LncRNA NR_136400 Suppresses Cell Proliferation and Invasion by Acting as a ceRNA of TUSC5 That Is Modulated by miR-8081 in Osteosarcoma - Liu, Liyun; Zheng, Mingxia; Wang, Xinwei; Gao, Yanzheng; Gu, Qingguo (Frontiers in Pharmacology, 2020)
Long non-coding RNAs (lncRNAs) are emerging as important regulators in cancerous formation and progression processes. The molecular mechanism of lncRNAs involving in the progression of osteosarcoma has not been clearly elucidated. The role of NR_136400, which was an uncharacterized lncRNA, has not been reported in osteosarcoma (OS) before. In the present study, we demonstrated that NR_136400 was downregulated in OS cells and its downregulation could promote OS cell proliferation, cell apoptosis and cell invasion. NR_136400 downregulation facilitated EMT by inhibiting E-cadherin and elevating the expression of ZEB1, Snail and Fibronection. In vivo experiment revealed that NR_136400 downregulation promoted tumor growth in OS using a xenograft tumor mouse model. Mechanistic investigations demonstrated that NR_136400 could competitively bind miR-8081 and then upregulated the protein expression TUSC5. Taken together, a newly identified regulatory mechanism of lncRNA NR_136400/miR-8081/TUSC5 axis was systematically studied in OS, which provides a promising target for therapeutic treatment.